1997
DOI: 10.1177/096368979700600506
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Encapsulated PC-12 Cells Demonstrate High-Affinity Uptake of Dopamine in Vitro and 18F-DOPA Uptake and Metabolism after Intracerebral Implantation in Nonhuman Primates

Abstract: Intracranial implantation of polymer-encapsulated PC-12 cells has been shown to improve motor behavioral performance in animal models of Parkinson's disease. The purpose of this blinded study was to examine whether such improvement is associated with the active uptake and metabolism of dopamine precursors by intracerebrally implanted polymer-encapsulated PC-12 cells. In an in vitro experiment we demonstrate that 3H-dopamine uptake by PC-12 cells was 10(8) fmol/min x 10(6) cells, and that this uptake can be spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Whether this is indeed the case, however, remains a subject of debate as studies are limited by the scarcity of efficient THz generating sources and sensitive detectors [6]. For example, human dermal fibroblasts exposed to continuous THz radiation from an optically pumped molecular gas THz laser source (2.52 THz, 227 mW/cm 2 ) for up to 80 min were shown to be 90% viable [10,11,12]. When exposed to the narrow-band THz radiation (2.3 THz, 1.4 W/cm 2 ), human embryonic stem cells (hESCs) showed no structural chromosomal aberrations or difference in cell morphology when compared to the untreated control, and only some minor upregulations of mitochondria-related genes were reported [1].…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is indeed the case, however, remains a subject of debate as studies are limited by the scarcity of efficient THz generating sources and sensitive detectors [6]. For example, human dermal fibroblasts exposed to continuous THz radiation from an optically pumped molecular gas THz laser source (2.52 THz, 227 mW/cm 2 ) for up to 80 min were shown to be 90% viable [10,11,12]. When exposed to the narrow-band THz radiation (2.3 THz, 1.4 W/cm 2 ), human embryonic stem cells (hESCs) showed no structural chromosomal aberrations or difference in cell morphology when compared to the untreated control, and only some minor upregulations of mitochondria-related genes were reported [1].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous and evoked release of dopamine can be detected from capsules maintained both in vitro, and following explantation from the CNS. Both rodent microdialysis and positron emission tomography (PET) studies in primates have confirmed that encapsulated PC12 cells continue to produce L-dopa / dopamine in situ [Tresco et al, 1992;Subramanian et al, 1997]. …”
Section: Immunoisolation Implant Tolerability and Longterm Protein Dmentioning
confidence: 99%
“…A left intracarotid infusion of MPTP was performed on the female rhesus monkey by a previously reported method, 30 several weeks prior to the PET study.…”
Section: N-methyl-2β-carbo-(s)-1′-fluoro-2-propoxy-3β-(4chlorophenyl)...mentioning
confidence: 99%